Uporaba načrtovanja poskusov in modeliranja z nevronsko mrežo pri določitvi recepture premaza z optimalnimi reološkimi in mehanskimi lastnostmi - Leskovšek, Nevenka (Kovine zlitine tehnologije, 1995)
A paint has to be regarded as a complex mixture of mutually interacting components, usually formulated for a specific application condition. The purpose of this work was an investigation of all influences of selected factors on mechanical and rheological properties (responses) of the high solid coating and to find the optimal formulation through neural network model. This approach allows to investigate each quality parameter (response) separately or all of them together, according to the variations of each component (factor) of the formulation. On the basis of the model properties are known for every formulation i.e. combination of factors within the area determined by the selected range of factors.
Keywords: modeliranje; nevronske mreže; mehanske lastnosti; nevronski modeli; reološke lastnosti; premazi